Pengaruh Tingkat Pemahaman Penumpang Terhadap Kepatuhan Regulasi Barang Berbahaya Pada Aturan Aviation Security Di Bandar Udara Sultan Muhammad Salahuddin Bima. - Muhlisa, Muhlisa; Nieamah, Kartika Fajar (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
This study aims to determine whether there is an effect of the level of passenger knowledge on the regulation of dangerous goods on Aviation Security rules at Sultan Muhammad Salahuddin Airport in Bima. This study uses quantitative methods in collecting data using the distribution of questionnaires to 100 passenger respondents at Sultan Muhammad Salahuddin Airport in Bima. The results showed that the level of understanding of passengers has a positive and significant influence on compliance with dangerous goods regulations in Aviation Security rules. With a t value of 18.690 which is greater than t table 1.984 and a significance value of 0.000 which is smaller than 0.05, which means Ho is rejected and Ha is accepted, and the coefficient of determination (R²) shows that the level of understanding is able to explain some of the compliance variables. This study confirms the need for increased socialization and education to passengers to increase compliance for flight safety.